Measurement of a country brand : the country brand strength index - Ribeiro, Bárbara Schoeppen de Magalhães Álvares (2017)
This thesis applies the Country Brand Strength Index (CBSI) developed by Marc Fetscherin in 2010, in a 5-year period analysis to conduct a longitudinal study applying it to 31 countries. The CBSI proposed is an alternative measurement to existing subjective survey-based measurement indexes. We want to raise the awareness of everyone of how important a country brand is in todays´ world. A strong country brand can stimulate exports, attract tourism, investments, and immigration. Countries need to understand that to stay competitive in the global economy they need to know how to assess their country brand to manage it in the most effective way. With the proposed CBSI, a country can identify its position, monitor its evolution over the years, and evaluate its competitive position relative to others. “A nation’s ‘brand’ exists, with or without any conscious efforts in nation branding, as each country has a current image to its international audience, be it strong or weak, clear or vague” (Fan, 2006). This thesis is divided into 4 main chapters, the first one outlines the goals and the methodology used, the second chapter provides an overall view of the concept of Country Branding and other related aspects, the third chapter covers all the details about the CBSI presented by Marc Fetscherin and the last chapter presents the empirical analysis where the CBSI was applied to new data with Portugal included. Finally, we outline the major conclusions and key areas to be considered in order for countries to leverage on this strategic dimension.